A history of wildfowl counts by The Wildfowl & Wetlands Trust - Cranswick, P A; Kirby, J S; Salmon, D G; Atkinson-Willes, G L; Pollitt, M S; Owen, M (Wildfowl, 1996)
A national scheme to monitor wildfowl was established in 1947 because of increasing conflicts between development and conservation needs and the lack of data with which to judge these issues objectively. Originally based at the Natural History Museum, responsibility for the scheme passed in 1954 to The Wildfowl Trust, now The Wildfowl & Wetlands Trust (WWT), which has played a central role in this and other waterfowl monitoring schemes ever since. This paper describes the growth and development of count schemes for wildfowl, and latterly waterfowl, principally in the UK but also internationally where WWT has played a pivotal role. The invaluable contribution made by the volunteer counter network is highlighted. The extent of the data gathered to date is summarised and examples are used to illustrate the general increase in wildfowl numbers in the UK over this period. The influence of the count scheme on the conservation of waterfowl and wetlands is also described.